CHILDREN WITH BIRTH DEFECTS; A CHALLENGE FOR PUBLIC HEALTH SERVICE (Proceedings of the International Conference on Public Health, 2023)
Children having birth defects denote a high risk group for oral diseases compared to their healthy counterpart. Untreated dental caries significantly accounts for the oral disease burden of children with birth defects. A preventive oral health and restorative dental care package with close follow up could offer much benefit for such children and this poster provides some baseline information in this regard. A Sample of 79 children with birth defects who visited the Preventive Oral Health Unit of the National Dental Hospital (Teaching) Sri Lanka from 1st January 2017 to 29th April 2019 were included in the present analysis, by extracting data from unit’s data base. The level of corporation of a child for oral health care was assessed by child’s compliance with mouth examination and provision of simple dental treatment in a child-friendly dental setting. Children with birth defects aged (mean ± SD) [6.02 ± 3.17-years], carried a high burden of untreated dental caries. The mean number (±SD) of non-cavitated decayed teeth was 2.65± 3.62, cavitated decayed teeth was 2.97±2.97 and pulp exposed teeth was 3.59 ±3.60 respectively. Children were offered a preventive oral health care package comprised of customized  behavioural management, oral hygiene instructions and  dietary counseling (for parental care givers), professional fluoride applications, simple restorations of carious teeth, fissure sealant applications for permanent molar teeth, referral for pulp therapy for pulp exposed symptomatic teeth under general anaesthesia to Restorative Unit B with follow up of care. 50.6% of children deemed cooperative and 8.9% were partially cooperative to receive oral health care provided by the Preventive Oral Health Unit. This baseline information must be utilized for effective planning of oral healthcare for children with birth defects.
Keywords: birth defects; oral diseases; oral health; oral hygiene